2017
DOI: 10.1111/echo.13546
|View full text |Cite
|
Sign up to set email alerts
|

Optimal right heart filling pressure in acute respiratory distress syndrome determined by strain echocardiography

Abstract: Our data are the first to show that an RV filling pressure of 13±2 mm Hg-as by CVP-correlates with optimal RV mechanics as evaluated by strain echocardiography in patients with moderate-severe ARDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
2
9
0
Order By: Relevance
“…Interobserver reproducibility assessed by ICC was > 0.75 for all LSS indices, which indicates good reliability [12], much higher than for RV FAC. The same findings were recently reported in ARDS patients by Garcia-Montilla et al, with high ICC coefficients for RV lateral strain but a low interobserver agreement for RVFAC [13]. This could be explained by the software-based automated tracing of the endocardial border, which limits operator dependency.…”
Section: Table 4 Correlation Coefficients (Pearson) Between Echocardisupporting
confidence: 85%
“…Interobserver reproducibility assessed by ICC was > 0.75 for all LSS indices, which indicates good reliability [12], much higher than for RV FAC. The same findings were recently reported in ARDS patients by Garcia-Montilla et al, with high ICC coefficients for RV lateral strain but a low interobserver agreement for RVFAC [13]. This could be explained by the software-based automated tracing of the endocardial border, which limits operator dependency.…”
Section: Table 4 Correlation Coefficients (Pearson) Between Echocardisupporting
confidence: 85%
“…These analyses demonstrated that an RVFWS of −21% (Figure 3, point A) corresponded to an LVEF of approximately 55% (vertical blue dotted arrow), and an LVGLS of −12% (Figure 3, point B) corresponded to an LVEF of approximately 42% (vertical red dotted arrow), and with an RVFWS close to −16% (Figure 3, point C). In a previous report, we demonstrated that in this group of patients with ARDS, the CVP values corresponding to points A and C on the RVFWS curve were approximately 13 mm Hg and 17 mm Hg, respectively 35 . The analyses of Figure 1 also suggested that points A and B represent two different inflection areas in the strain function curves of RV and LV correspondingly, and the distance and slope between these two points signify a period of progressive biventricular contractile deterioration.…”
Section: Resultssupporting
confidence: 51%
“…From a practical perspective, our results indicate that in moderate–severe ARDS, the sole presence of a nondilated IVC is associated with a preserved cardio‐circulatory function and, in this circumstance, intravenous fluids may be confidently given with an potentially expected good clinical response and tolerance. However the development of a dilated IVC, more if associated with a significantly elevated CVP, 35,46,48 may be a marker of imminent circulatory failure, and should signal the necessity to stop fluid expansion, initiate diuretic administration, 47 or renal replacement therapy 12,13 and consider the initiation/escalation of vasoactive drugs, 14 while fine tuning other cardiac (particularly right ventricle) protecting interventions such as ventilatory optimization, hypercarbia limitation, and/or the initiation of prone position ventilation 31,57,58 …”
Section: Discussionmentioning
confidence: 99%
“…It has also demonstrated a close association with invasively measured cardiac index (54) and RV stroke work index (53,54). Recently, Garcia-Montilla and colleagues (55) evaluated whether RVFWS was able to predict an optimal RV filling pressure in patients with ARDS receiving lung protective MV (55). These authors concluded that in terms of RV mechanics, the optimal RV filling pressure in moderate-severe ARDS may typically average CVP of ~13 mmHg, and correlating with a RVFWS of ~20% (normal reference value) (55).…”
Section: The Role Of Echocardiographymentioning
confidence: 99%
“…Recently, Garcia-Montilla and colleagues (55) evaluated whether RVFWS was able to predict an optimal RV filling pressure in patients with ARDS receiving lung protective MV (55). These authors concluded that in terms of RV mechanics, the optimal RV filling pressure in moderate-severe ARDS may typically average CVP of ~13 mmHg, and correlating with a RVFWS of ~20% (normal reference value) (55). Once this technology becomes more widely available and standardized, STE may provide critical care practitioners with an important and objective metric to help with hemodynamic management of patients with ARDS, potentially allowing, for example, realtime PEEP titration based on RV strain.…”
Section: The Role Of Echocardiographymentioning
confidence: 99%